GROWTH AND BEHAVIOURAL PATTERNS OF FEMALE CROSS-BRED CALVES UNDER DIFFERENT SHELTER MANAGEMENT PRACTICES DURING WINTER SEASON (Indian Journal of Animal Production and Management, 2016)
Fifteen crossbred calves were divided into 3 groups of 5 animals each on the basis of their similar body weight  and age. Each group was allotted to three housing system viz. (T1, loose house; T2, loose house + bedding +  curtains and T3 ,conventional barn) during winter season. Average maximum temperature was significantly  (P
Keywords: Barn house; Bedding; Behaviour; Crossbred calves; Curtains; Growth; Loose house